FASHOHATUL MUFROD (TANAFURI AL-HURUF, GHARABAH, MUKHOLAFATU AL-QIYAS) - Eni Misna; Candra Widana (Jurnal Akademika Kajian Ilmu-Ilmu Sosial, Humaniora Dan Agama, 2026)
Fashahatul mufrod is a branch of balaghah that examines linguistic eloquence as the key to the beauty and miraculous nature of the Qur’an. This study aims to examine fashahah al-mufrod along with its three main pillars: tanafuri al-huruf, gharabah, and mukhalafatu al-qiyas. The method used is qualitative research with a literature review approach through data collection from the Qur’an, classical balaghah texts, and related journals. The results of the study indicate that fashahah al-mufrod has developed as a systematic concept through the thought of balaghah scholars, freeing individual words from phonetic difficulties, semantic rigidity, and deviations from grammatical rules. Theoretically, this eloquence is divided into fashahah al-kalimat, al-kalam, and al-mutakallim, which play a crucial role in creating aesthetic harmony, ease of memorization, and the rhetorical power of the Qur’anic language.